2021
DOI: 10.3389/frai.2021.668215
|View full text |Cite
|
Sign up to set email alerts
|

Solution of the Fokker–Planck Equation by Cross Approximation Method in the Tensor Train Format

Abstract: We propose the novel numerical scheme for solution of the multidimensional Fokker–Planck equation, which is based on the Chebyshev interpolation and the spectral differentiation techniques as well as low rank tensor approximations, namely, the tensor train decomposition and the multidimensional cross approximation method, which in combination makes it possible to drastically reduce the number of degrees of freedom required to maintain accuracy as dimensionality increases. We demonstrate the effectiveness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Proof The equivalence between (47) and ( 48) is an immediate consequence of (7). We now prove that ( 46) is equivalent to (47).…”
Section: Proposition 3 (Geometric Interpretation Of Rank Addition) Letmentioning
confidence: 76%
See 1 more Smart Citation
“…Proof The equivalence between (47) and ( 48) is an immediate consequence of (7). We now prove that ( 46) is equivalent to (47).…”
Section: Proposition 3 (Geometric Interpretation Of Rank Addition) Letmentioning
confidence: 76%
“…In order to reduce the number of degrees of freedom in the solution tensor f (t), we seek a representation of the solution on a low-rank tensor format [7,13,22] for all t ≥ 0. To complement the low-rank structure of f (t), we also represent the operator N in a compatible low-rank format, allowing for an efficient computation of N( f (t)) at each time t in (2).…”
Section: Introductionmentioning
confidence: 99%
“…In References 15‐17, it was observed that the straightforward application of TT optimization‐based solvers to linear systems arising from PDEs with matrices in the QTT format, leads to severe numerical instabilities. This problem was formalized in Reference 18 and originates from both ill conditioning of discretized differential operators and the ill conditioning of the tensor representations themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Tensor networks have been successfully applied to a wide range of studies, including applications to solving partial differential equations, quantum dynamics methods, machine learning, electronic structure calculations, and calculations of vibrational states. …”
Section: Introductionmentioning
confidence: 99%